A Second Chance: The University of Cape Town's Diploma in Education - June Saldanha (Gateways, 2009)
This paper describes a curriculum that gives men and women from predominantly black working class communities a second chance to acquire a formal qualification at a higher education institution in South Africa. The curriculum provides the space for adult students to think critically about themselves and their practice and to develop a confident voice to express themselves. Through this process they develop both learner and educator identities and begin to see how the two intersect. The paper gives some of the historical background of the course, and shows how lecturers who have taught on the programme at different times have helped shape the curriculum. It goes on to discuss the changing nature of the student intake, the curriculum content and structure and ends with a discussion of the impact of the course, on students, staff and on the university as a whole. One very visible impact of the diploma is to be seen in the students who have gone on to acquire other postgraduate qualifications in adult education studies. On a university-wide level, through the involvement of adult education lecturers in other programmes and curricula, knowledge of and interest in adult learning is shared and encouraged.